Anwendung und Interpretation der R‑Klassifikation beim Lungenkarzinom: Ergebnisse einer Umfrage an zertifizierten Lungenkrebszentren = Application and interpretation of the R classification for lung cancer : Results of a survey of certified lung cancer centers - Hoffmann, Hans; Warth, Arne (Der Pathologe, 2016)
The residual (R) tumor classification is an essential, even if facultative component of the TNM classification; however, it should alway be included in the pathology results of certified lung cancer centers. In discussions it becomes clear again and again that different hospitals and departments have different approaches and interpretations with respect to the R status after lung resection. We carried out a questionnaire-based survey of pathologists (with specialization in pulmonary pathology) and thoracic surgeons on the application of the R classification for lung tumors. The results of the survey revealed the different perceptions of the participating centers with respect to application and interpretation, which results in divergent decisions for adjuvant therapy and complicates the comparability of national and international studies. The results of the survey are especially valuable because all participants have a high level of expertise in the field of thoracic pathology and the data reflect the current practice in certified lung cancer centers. It appears to be necessary to examine the application and interpretation of the R classification for lung cancer more closely in an interdisciplinary exchange and to produce a catalogue of criteria to guarantee at least a better national standardization.
Gesehen am 23.10.2019